The Postmodern Condition - Stanishev, Georgi (project baikal, 2019)
The interview with a famous theorist of architecture, researcher of postmodernism Charles Jencks is a part of the book “Architectural Theories in Monologues” by Prof. G. Stanishev. In the conversation conducted in a free tone, Charles Jencks shares his thoughts on the matter of postmodernism and its relations with the previous stages of development of architectural thought.